Analysis of information literacy competencies assessment studies submitted to the University of the Philippines School of Library and Information Studies (2002-2016) - Domingo, Angelee S.; Santos, Yhna Therese P.; Obille, Kathleen Lourdes B.; Lapuz, Elvira B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Information literacy is a fundamental skill and forms the foundation of an individual for lifelong learning and essential for adapting in today's modern society. Technology is rapidly growing, thus, information literacy skills are vital in order to adjust to this kind of environment full of plethora of information. It includes recognizing when information is needed and being able to efficiently locate, correctly evaluate, effectively use, and clearly link information in several formats. Students today face a daily explosion of information resources and the challenge of using these resources effectively and responsibly.
Assessment is a method in which goals and learning objectives of a program or course are recognized and data are collected from several sources to document student, teacher, or program achievement of those goals and objectives.
While there are standards for information literacy instruction, varying approaches to its implementation is evident. As such, with the many researches done pertaining to information literacy, varying methodologies, coverages and variables can be seen. This study determined the extent of research in information literacy competency among the submitted theses to the UP SLIS from 2002-2016 and data collection was done through meta-analysis in the UP SLIS Library covering a total of 7 undergraduate and 2 graduate theses.
The common contributing standards, approaches and strategies in determining the levels of information literacy competencies of students in private and public secondary and tertiary schools based on the studies submitted to the UP SLIS are the following; objectives, methodologies, instruments used, standards/models used, and population/respondents. The common demographic factors that influenced the results of these studies are the following; Grade School students (General), High School students (General), HS Year level specified, College student (General), College year level specified and Gender.
The resemblance and variants with the results and recommendations have demonstrated that all IL studies have the same objectives and outcomes on the information literacy competency skills assessment result (rating, level, passed, failed, etc.). Similar with the methodologies employed and instruments used, all IL studies facilitated the same procedures. On the other hand, the implication and usage of demographic factors differ greatly with each study. Same goes with the conclusions which significantly differed and was unexpected because as stated above, all studies have the same objectives and outcomes. As libraries have different assessment needs, it is important to continue conducting information literacy competency assessments. There is no one-size, fits all in assessment. Consequently, a good information literacy program can be developed after assessing full IL skills of the students and determine which skills need more attention.
"modern society. Technology is rapidly growing, thus, information literacy skills are vital in order to adjust to this kind of environment full of plethora of information. It includes recognizing when information is needed and being able to efficiently locate, correctly evaluate, effectively use, and clearly link information in several formats. Students today face a daily explosion of information resources and the challenge of using these resources effectively and responsibly. Assessment is a method in which goals and learning objectives of a program or course are recognized and data are collected from several sources to document student, teacher, or program achievement of those goals and objectives. While there are standards for information literacy instruction, varying approaches to its implementation is evident. As such, with the many researches done pertaining to information literacy, varying methodologies, coverages and variables can be seen. This study determined the extent of research in information literacy competency among the submitted theses to the UP SLIS from 2002-2016 and data collection was done through meta-analysis in the UP SLIS Library covering a total of 7 undergraduate and 2 graduate theses. The common contributing standards, approaches and strategies in determining the levels of information literacy competencies of students in private and public secondary and tertiary schools based on the studies submitted to the UP SLIS are the following; objectives, methodologies, instruments used, standards/models used, and population/respondents. The common demographic factors that influenced the results of these studies are the following; Grade School students (General), High School students (General), HS Year level specified, College student (General), College year level specified and Gender. The resemblance and variants with the results and recommendations have demonstrated that all IL studies have the same objectives and outcomes on the information literacy competency skills assessment result (rating, level, passed, failed, etc.). Similar with the methodologies employed and instruments used, all IL studies facilitated the same procedures. On the other hand, the implication and usage of demographic factors differ greatly with each study. Same goes with the conclusions which significantly differed and was unexpected because as stated above, all studies have the same objectives and outcomes. As libraries have different assessment needs, it is important to continue conducting information literacy competency assessments. There is no one-size, fits all in assessment. Consequently, a good information literacy program can be developed after assessing full IL skills of the students and determine which skills need more attention. "
Special Problem
Keywords: Information literacy -- Standards; Information literacy